A 28.7V Modular Supply Multiplying Pulser with 75.4% Power Reduction Relative to CV2f - Choi, Kyu Jin; Yeo, Hong Goo; Choi, Hongsoo; Jee, Dong Woo (IEEE Transactions on Circuits and Systems II: Express Briefs, 2021)
This brief presents a high voltage modular supply multiplying pulser in a 0.18-μ m BCD CMOS process. Two prototypes of the pulser were implemented for target loads of 55pF and 1nF, and generated up to 1MHz and 28.7V pulse from 1.2 and 5V supplies. Proposed modular based stepwise pulse generation achieved a peak power reduction of 75.4% relative to CV2 f and a peak power efficiency of 82.3%. The proposed pulser was used for driving piezoelectric micromachined ultrasound transducer (pMUT) and achieved a relative efficiency improvement of 113.7% against conventional two-level square wave pulsing.
Keywords: CMOS processs; High voltage; Micromachined ultrasound transducers; Peak power reduction; Power reductions; Pulse generation; Relative efficiency; Square waves; high efficiency; high power reduction; high-voltage pulse; low supply voltage; modular architecture; Pulse generation; supply voltage multiplying